UNCCD COP16 side event: CGIAR and ILC driving international collaboration for local solutions on land and natural resource tenure - Onyango, Polycarp Otieno (CGIAR System Organization, 2024)
At the UN Convention to Combat Desertification (UNCCD) COP 16 in Riyadh, CGIAR and the International Land Coalition (ILC) co-hosted a side event on ‘Land and Natural Resource Tenure’. The event highlighted how CGIAR’s recent membership in ILC could open opportunities to scale research on land and natural resource governance, tenure, and planning – essential building blocks for sustainable agrifood systems.